Feast or famine : food and drink in American westward expansion - Horsman, Reginald (University of Missouri Press, 2008)
"Drawing on the journals and correspondence of pioneers, Horsman examines more than a hundred years of history, recording components of the diets of various groups, including travelers, settlers, fur traders, soldiers, and miners. He discusses food-preparation techniques, including the development of canning, and foods common in different regions"--Provided by publisher